Upregulation of the Tim-3/Gal-9 pathway and correlation with the development of preeclampsia. (November 2015) - Hao, Haiyan; He, Mengzhou; Li, Jing; Zhou, Yuan; Dang, Jing; Li, Fanfan; Yang, Meitao; Deng, Dongrui
Abstract: Objective: It is well documented that an imbalance in immune tolerance at the maternal–fetal interface is likely to play an essential role in the etiology of preeclampsia. However, the mechanisms underlying immune tolerance during preeclampsia are still poorly understood. Tim-3, a Th1-specific cell surface molecule, is a relatively newly described molecule with important immunological functions. It can regulate Th1 responses with its ligand galectin-9 (Gal-9), and has become an attractive candidate for exploring the pathogenesis of preeclampsia. Study design: Twenty normal pregnancies and 20 preeclamptic pregnancies were enrolled in the present study. We examined the expression and function of Tim-3/Gal-9 in decidual tissue at the RNA and protein levels. In order to analyze their correlation with the development of preeclampsia, we measured the expression of Tim-3 on peripheral blood leukocytes using flow cytometry. IFN-γ, IL-10, and IL-17 in the peripheral blood plasma were measured by ELISA. Results: Tim-3/Gal-9 was upregulated in decidual tissue of preeclamptic vs. normotensive pregnancies. There was a significantly increased Th1 and Th17 response in PE as demonstrated by the upregulated levels of IFN-γ/IL-17, whereas IL-10 secreted by Th2 cells was sharply reduced. Conclusions: The present study showed that an abnormal Tim-3/Gal-9 pathway was able to facilitate the development of preeclampsia. Our data uncovered a novel mechanism by which the Tim-3/Gal-9 pathway regulates immune responses, and we now identify this pathway as a potential therapeutic target in preeclampsia.